Blocking amino acid transporter OsAAP3 improves grain yield by promoting outgrowth buds and increasing tiller number in rice - Lu, Kai; Wu, Bowen; Wang, Jie; Zhu, Wei; Nie, Haipeng; Qian, Junjie; Huang, Weiting; Fang, Zhongming (Plant biotechnology journal, 2018)
Summary Amino acid transporters (AATs) play indispensable roles in nutrient allocation during plant development. In this study, we demonstrated that inhibiting expression of the rice amino acid transporter OsAAP3 increased grain yield due to a formation of larger numbers of tillers as a result of increased bud outgrowth. Elevated expression of OsAAP3 in transgenic plants resulted in significantly higher amino acid concentrations of Lys, Arg, His, Asp, Ala, Gln, Gly, Thr and Tyr, and inhibited bud outgrowth and rice tillering. However, RNAi of OsAAP3 decreased significantly Arg, Lys, Asp and Thr concentrations to a small extent, and thus promoted bud outgrowth, increased significantly tiller numbers and effective panicle numbers per plant, and further enhanced significantly grain yield and nitrogen use efficiency (NUE). The promoter sequences of OsAAP3 showed some divergence between Japonica and Indica rice, and expression of the gene was higher in Japonica, which produced fewer tillers than Indica. We generated knockout lines of OsAAP3 on Japonica ZH11 and KY131 using CRISPR technology and found that grain yield could be increased significantly. These results suggest that manipulation of OsAAP3 expression could be used to increase grain yield in rice.